Pengaruh Pemberian Ekstrak Etanol Herba Meniran Etanol Herba eniran (Phyllanthus niruri) Terhadap Aktivitas Fagositosis Makrrofag Mencit Swiss yang Diinfeksi Plasmodium berghei = The Effect of the Administration of ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract This studies was carried out to evaluate the influence of ethanol extract ofPhyllanthus niruri (EEPN) to the macrophage phagocytosis activity of male Swiss mice during P. berghei infection.The laboratory experimental research conducted on 75 male Swiss mice divided in five group. The group one to three as experimental group were ingested EEPN 5,10 and 100 mg/kgBW/ day respectively. The group four as positive control group is ingested malaria vaccine P. berghei on erithrocyte stadium and the group as hegative control group is ingested water. The EEPN, malaria vaccine and water is mgested during fourteen day. On the fourteenth daye ach group was infected by P. berghei. The phagocytosis activity of macrophage response was observed on the zeroth, second, fifth, and the seventh day after the infection. The macrophage phagocytosis activity response was evaluated with latex test and parasitemia level of the tested animal. The data was processed with SPSS program